CONSTRUCTION OF BLUE ECONOMY DEVELOPMENT INDEX AT THE PROVINCIAL LEVEL IN INDONESIA USING EXPLORATORY FACTOR ANALYSIS - Dewi Novita Sari; Siskarossa Ika Oktora (Barekeng)
Indonesia, as an archipelagic country, holds marine resources of significant economic value in improving the welfare of its people. However, the community's use of marine resources does not pay attention to sustainability. The government then uses the Blue Economy concept to maximize the economic value obtained while maintaining the sustainability of the marine ecosystem through national policies and plans. In realizing blue economy development, enabler factors, such as technology and government governance, have an important role. This research aims to construct a Blue Economy Development Index (IPEB) at the provincial level in Indonesia in 2021, including enabler factors for blue economy development. The analytical method used is Exploratory Factor Analysis. The results show that the distribution of the minimum values for the indicators that make up the IPEB is found in the provinces of the Eastern Region of Indonesia. In contrast, the distribution of the maximum values of the indicators is found in the provinces of the Western Region of Indonesia. The province with the highest IPEB score is South Sulawesi, while the lowest is Central Sulawesi. The limitation of this study is the data derived from the Village Potential Survey (Potensi Desa) data collection, so several variables are not yet available in annual time. The results of this study are important in improving the ability to monitor implementation and assist in decision-making in increasing blue economic development, especially at the provincial level.